Correlation of PDL-1 Expression with Tumour Budding and Tumour Infiltrating Lymphocytes in Colorectal Cancers - Singh, Tejasvita; Singh, Anshul; Bind, Manoj; Misra, Vatsala; Misra, S.P.; Dwivedi, Manisha; Ahmad, Shabi (Asian Pacific Journal of Cancer Biology, 2023)
Objective: To study and correlate PDL-1 expression with Tumour budding and Tumour Infiltrating Lymphocytes in Colorectal Carcinoma. Background: Colorectal cancer (CRC) is third most common cancer with a high mortality. Many attempts have been made to raise overall survival of CRC patients. The immune system plays an important role in clearing the unhealthy cancer cells. Programmed death 1 (PD1) is a regulatory molecule which dampens the immune response when bound to one of its complementary ligands (PDL1). Its expression is related to the response of immunotherapy in CRC treatment which has been exploited in recent times. However, its prognostic value is still controversial, and the distribution of PD-L1 on tumour Cells or Immune Cells has not been comprehensively analysed. Method: A total of 30 patients diagnosed with CRCs were included who underwent surgical intervention. Cases who took preoperative neoadjuvant chemotherapy or radiotherapy were excluded. IHC analyses of PDL1 was done and was correlated with tumour budding and Tumour Infiltrating Lymphocytes (TILs) and statistical significance was assessed. Results: 11 cases showed low bud count at the invasive front out of which only 3 cases showed PDL1 positivity. The rest 19 cases had high bud count out of which 18 were PDL 1 positive. This difference was highly significant (p = 0.002). In Low Bud / High TILs, 75% cases showed no PDL1 expression in tumour cells, whereas 62.5% cases showed PDL1 positivity in TILs whereas in High Bud / Low TILs group, all the cases (100%) showed PDL1 expression in tumour cells whereas only 75% cases showed PDL1 positivity in TILs, again being statistically significant (p <0.001). Conclusion: This study showed an inverse correlation between PDL1 in tumour buds and immune cells, thus emphasising the role of tumour microenvironment. Our study reiterates the fact that high expression of PDL1 in tumour cells suppresses antitumor response whereas its high expression in TILS correlates with a better prognosis.